Analisa Persimpangan Jalan Tanpa Sinyal (Studi Kasus Simpang Tiga Jalan Sematang Borang - Jalan Siaran Kota Palembang) - Eko Nurrahman; Pujiono Pujiono; Robi Sahbar (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Roads are a crucial element in land transportation infrastructure that require special management, particularly at intersections between two or more road sections. Urban development in Palembang City has led to a significant increase in population mobility and vehicle volume, particularly in areas with growing residential and commercial activity. This issue is crucial for further study, given their function as connecting routes between densely populated residential areas and community activity centers. Considering these conditions, the author was motivated to conduct a study entitled "Analysis of Unsignalized Road Intersections (Case Study of the Sematang Borang and Siaran Road Intersections, Palembang City"). This study aims to obtain data on traffic flow, intersection capacity, degree of saturation, vehicle delays, and the probability of queuing using the PKJI (Indonesian Road Capacity Guidelines 2023) calculation analysis. From the results of this study, it shows that at the three-way intersection without Sematang Borang road signal – Siaran road, the highest vehicle volume occurs in the afternoon (17.00-18.00 WIB), amounting to q = 4659 SMP / hour, the intersection capacity value is C = 2801.80 SMP / hour, the delay value T = - 12.678 seconds / Vehicle, and the queue opportunity value Pa = 120.217%. Judging from the saturation degree value that exceeds the intersection plan performance value of 0.85, it shows that the intersection performance condition is almost saturated or congested, to the point of experiencing delays and vehicle queues.